(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Fabric and garment drape were compared using an alternative drape measurement system based on an image analysis technique. Garment drape was investigated using dresses suspended on a mannequin. A graphical user interface was developed to carry out the image analysis and to calculate drape values identifying and determining 21 parameters. A range of fabrics including knitted, woven and nonwoven fabrics were compared in terms of FAST properties, drape coefficient and drape values. Visual assessment of the fabric range was carried out in terms of drape amount and preference. Low agreement was found between individuals with regard to preferred drape amount and high agreement with respect to actual drape amount. Nonwovens were found of better preference over some traditional fabrics. Most of the drape values of fabric and garment were found to have poor correlations.